1999
DOI: 10.1046/j.1365-2133.1999.02930.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of abnormal keratinocyte differentiation in molluscum contagiosum

Abstract: To investigate abnormalities in the keratinization process in lesional epidermis of molluscum contagiosum, production of filaggrin, loricrin, Ted-H-1 antigen, involucrin, cystatin A and CD95 ligand (CD95L) was investigated using specific antibodies. Anti-filaggrin monoclonal antibody (MoAb) did not react with keratohyalin granules (KHG), but with the substance around virus particles in the stratum corneum. KHG reacted with anti-loricrin polyclonal antibody (PoAb) and anti-Ted-H-1 MoAb. Anti-involucrin PoAb and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…From a kinetic point of view, the pathogenesis of molluscum contagiosum is poorly understood. Acanthosis, large keratohyalin granules and lack of reactivity of the keratohyalin granules to antifilaggrin monoclonal antibodies have suggested that the pathogenesis of molluscum contagiosum may involve abnormal differentiation of epidermal cells 2 . It is conceivable that activation/ inactivation of tumour suppressor genes or of cellular oncogenes plays a role in the pathogenesis of molluscum contagiosum lesions.…”
mentioning
confidence: 99%
“…From a kinetic point of view, the pathogenesis of molluscum contagiosum is poorly understood. Acanthosis, large keratohyalin granules and lack of reactivity of the keratohyalin granules to antifilaggrin monoclonal antibodies have suggested that the pathogenesis of molluscum contagiosum may involve abnormal differentiation of epidermal cells 2 . It is conceivable that activation/ inactivation of tumour suppressor genes or of cellular oncogenes plays a role in the pathogenesis of molluscum contagiosum lesions.…”
mentioning
confidence: 99%
“…The virus of MC has not been grown in tissue culture. [34] Histological examination after haematoxylin and eosin staining confirmed that the proliferative lesion was due to MC, and demonstration of the presence of molluscum bodies in a section can be revealed by in situ hybridization. Sequence analysis in the polymerase chain reaction is more sensitive than in situ hybridization and in dual infection with both MCV and Human papillomavirus (HPV) , the immunosuppressive genes of Molluscipox virus could enhance survival of the oncogenic types of HPV.…”
Section: Considerations On Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…Abnormal keratinization process in lesional epidermis of MC can be proved by specific antibodies to filaggrin, loricrin, Ted-H-1 antigen, involucrin, cystatin A, and CD95 ligand. [26,34] Cell-mediated immunity seems to be important in host defence. The virus of MC has not been grown in tissue culture.…”
Section: Considerations On Diagnosis and Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the acute generalized infection with high mortality caused by variola virus, MCV produces a chronic infection localized to epidermal tissue (10,27). This is characterized by hyperplasia and hypertrophy of the virusinfected keratinocytes (7,35,37), and MCV-infected tissue shows an abnormal expression of proteins of the cytoskeleton and cell cycle (35,37). In the absence of a functional immune system, MCV causes giant molluscum, with extensive disfiguring lesions (19).…”
mentioning
confidence: 99%